Religion, Education and Peace - Herzerger, Radhika (JOURNAL OF INDIAN EDUCATION, 2007)
Religion today has become an easy outlet through which people vent their hatred and thus become a source of violence ironically against its very essence of universal love and peace. Since hatred and violence are rooted in greed, turn up in the most insidious forms within the individual self, education has an important role in inculcating the values of peace among the students while unlearning greed and aggression. The presentation espouses the educational philosophy of Jiddu Krishnamurti’s and the Rishi Valley School, a project guided by his philosophy to promote the culture of peace. In the wake of the growing problems brought with the assertion of renewed identities founded on religion and also the various problems resulting from human negligence, for example, the degrading eco-system, etc. Krishnamurti’s vision could be translated into reality of today.